Challenges and Strategies for Human Resource Development in Islamic Education: A Case Study of MAN 1 Lamongan - Moh Romzi; Siswanto; Wiwik Wida Farwati; Sholeh; Afif Fariqi; M. Adi Kulsum (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
This study explores the implementation of human resource development (HRD) at MAN 1 Lamongan using a qualitative case study approach. The research aims to describe how both internal and external strategies are employed to enhance the competencies of educators and educational staff. Data were collected through in-depth interviews, participatory observation, and document analysis. The data analysis followed the interactive model of Miles, Huberman, and Saldana, comprising data condensation, data display, and conclusion drawing. The findings reveal that MAN 1 Lamongan adopts a dual HRD strategy. Internally, the institution organizes regular training programs, workshops, and seminars at least twice a year. Externally, it facilitates staff participation in training activities provided by external organizations, such as MGMP forums and specialized professional courses. Each initiative is preceded by a needs analysis and followed by implementation and evaluation phases. The institution integrates both on-the-job and off-the-job training methods to improve pedagogical, managerial, and technical competencies. This comprehensive and continuous professional development approach is aligned with institutional goals and the evolving needs of educators. The study offers practical insights for Islamic educational institutions in designing effective HRD frameworks. However, as the research focuses on a single institution, its findings may have limited generalizability. Future studies involving multiple madrasas are recommended to validate and expand the applicability of the proposed model in diverse educational contexts.